The Role Of The Investigative Audit Report Of The Supreme Audit Agency In Proving Corruption - Hendri, Fahzal; Maryano, Maryano; Nara, Vicheth (CV. Era Digital Nusantara, 2024)
This study aims to analyze the factors that influence corruption in Indonesia, as well as the role of the Supreme Audit Agency (BPK) in law enforcement and state financial management. Using a qualitative approach and normative legal analysis, this research finds that corruption has various forms and typologies regulated in Law No. 31 of 1999. BPK plays an important role in identifying state losses through the Audit Report (LHP), which serves as evidence in handling corruption cases. This research recommends improvements in the legal system and capacity building of the BPK as well as cooperation with law enforcement officials to effectively achieve the goal of eradicating corruption